Effect extract of Ipomoea pes-caprae leaf as anti-inflammatory non immunological in rat Rattus norvegicus - Safrida Safrida; Hasanuddin Hasanuddin; Nurul A. Agusdinianti (Syiah Kuala University, 2019)
Ipomoea pes-caprae is one of the plants in Indonesia that has the potential as a traditional herbal medicine to treat inflammation. Hence, the objective of this study was to evaluate the effect of I. pes-capraeleaf extract as anti-inflammatory in edema rats induced by 5% egg white solution. The experimental design used was a Completely Randomized Design (CRD) consisted of 5 treatments, each consisted of 5 rats.The treatment consisted of KN = negative control, KP = positive control, giving of 25 mg diclofenac sodium, K 100 = giving 100 mg kg-1body weight (BW) of I. pes-capraeleaf extract , K300 = 300 mg kg-1BW of I. pes-capraeleaf extract, and K500 = 500 mg kg-1BW of I. pes-capraeleaf extract. The anti-inflammatory data obtained were tested statistically with a one-way ANOVA test at 99% confidence level and followed by Duncan's test. The ANOVA test results showed that the giving ofI. pes-capraeleaf extract had a very significant effect (p 0.01) on the percentage of inflammatory, obtained Fcount Ftable, 21.46 4.79 at the level of α = 0.01. The treatment of I. pes-capraeleaf extract of 500 mg kg-1BW had the effect of decreasing the volume of edema with the positive control variable using diclofenac sodium 25 mg. It is concluded that I. pes-capraeleaf extract can be used as an anti-inflammatory by decreasing rat feet edema volume. I. pes-capraeleaf extract has a prospect for non-immunological inflammatory natural drug candidates.